A walk across the sun a novel - Addison, Corban 1979- (New York, NY SilverOak, 2012)
When a tsunami rages through their coastal town in India, 17-year-old Ahalya Ghai and her 15-year-old sister Sita are left orphaned and homeless. As they struggle to reach the safe haven of the convent where they attend school, they are abducted by human traffickers and thrust into a hidden world of sexual violence and illicit commerce, where the most valuable prize is the innocence of a child. Halfway across the world, in Washington, D.C., attorney Thomas Clarke faces his own personal and professional crises. Haunted by the tragic death of his infant daughter and estranged from his wife, he makes the fateful decision to pursue a pro bono sabbatical in India with an NGO that prosecutes the subcontinent's human traffickers. In Mumbai, his conscience awakens as he sees firsthand the horrors of the sex trade and the corrupt judicial system that fosters it. When he learns the fate of Ahalya and Sita, Clarke makes it his personal mission to rescue them, setting the stage for a deadly showdown with an international network of ruthless criminals. Spanning three continents and two cultures, this story chronicles an unforgettable journey through the underworld of modern slavery and into the darkest and most resilient corners of the human heart
1 14
NEW, LITERATURE
Keywords: Child trafficking victims -- Fiction; Disaster victims -- India -- Fiction; Human trafficking -- India -- Fiction; Sisters -- India -- Fiction; Teenage girls -- India -- Fiction; Tsunamis -- India -- Coromandel Coast -- Fiction; Atlanta (Ga.) -- Fiction; Tamil Nadu (India) -- Fiction; Domestic fiction; Psychological fiction